Differential Occurrence Characteristics and Influence Factors of Reservoir Movable Fluids in Tight Gas: A Case Study of Shan 1 Reservoir in Yanchang Area. (21st March 2023) - Liu, Jiangbin; Wu, Xiaobin
Abstract : The occurrence characteristic of movable fluid is a crucial index for tight sandstone reservoir evaluation, and the study of the differential occurrence of reservoir movable fluid is vitally important for the exploration and development of tight gas. Therefore, on the basis of casting thin section, scanning electron microscope, X-ray diffraction, high-pressure mercury injection, and nuclear magnetic resonance testing, the differential occurrence characteristics and influencing factors of reservoir movable fluid are analyzed based on the reservoir of Shan 1 reservoir. The results show that the main types of Shan 1 reservoir are lithic quartz sandstone and lithic sandstone, and intergranular solution pores and cutting solution pores are mainly developed in Shan 1 reservoir in Yanchang area. The movable fluid saturation of Shan 1 reservoir is 21.64% 69.62%, and the average of the movable fluid saturation is 35.32%. Most of the T 2 spectra are unimodal. According to the pore development, the reservoir is divided into four types, and fluid flow property in reservoir varies with the difference of reservoir pore development. Sandstone types, reservoir porosity, permeability, pore type, pore throat parameters, and cement content affect movable fluid saturation. The pores provide the main space for the movable fluid. The better the development of intergranular solution pores, the larger the average pore throat radius and the higher the movable fluid saturation of the reservoir. The higher the content of the calcite, the more obvious pore loss of the reservoir and the lower movable fluid saturation in the reservoir. The higher the content of illite, the worse the pore evolution and the lower fluid flow property in reservoir.